Legal Agreement on Supreme Court Decision Number 2992 K/Pdt/2015: Legal Issues in Capital Goods Sale and Purchase Agreements reviewed from International Civil Law - Fitri Setyo Rini; Rina Arum Prastyanti (Indonesian Journal of Law and Justice, 2024)
This study highlights the importance of understanding the dynamics of international civil law in the context of capital goods sale and purchase agreements, emphasizing the legal analysis of the Supreme Court Decision Number 2992K/Pdt/2015. In the era of globalization, capital goods sale and purchase agreements are increasingly complicated because they involve various legal systems, standards, regulations, and the process of converting foreign currency to rupiah. This study identifies various legal issues that arise in international capital goods sale and purchase agreements, such as differences in legal interpretations between countries and fluctuations in currency exchange rates. Using the normative legal method, this study analyzes how the Supreme Court applies the principles of international treaty law to address these issues. The results show that this Supreme Court Decision makes an important contribution to the development of international capital goods sale and purchase agreement law in Indonesia, especially in strengthening the rules on the use of the rupiah currency in domestic transactions. This study also emphasizes the need for clear contracts and compliance with the rule of law to prevent future disputes.